2012
DOI: 10.1007/s10552-012-9990-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary cancers among colorectal cancer survivors in Queensland, Australia, 1996–2007

Abstract: While these population-based results do not incorporate all possible risk factors, they form an important foundation from which to further investigate the etiological causes that result in the development of MPCs among colorectal cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(70 reference statements)
2
10
0
Order By: Relevance
“…In the present study, we demonstrated that the incidence of SPMs is higher in patients with CRC than in the general population (SIR = 1.13). In addition to the SPMs previously reported, 7 , 9 , 10 we found an increased risk for bone and soft tissue cancers in patients with CRC. Of note, opposite risks for a second liver cancer were observed in subgroup analysis.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In the present study, we demonstrated that the incidence of SPMs is higher in patients with CRC than in the general population (SIR = 1.13). In addition to the SPMs previously reported, 7 , 9 , 10 we found an increased risk for bone and soft tissue cancers in patients with CRC. Of note, opposite risks for a second liver cancer were observed in subgroup analysis.…”
Section: Discussionsupporting
confidence: 68%
“…Stratified age analysis demonstrated that the relative risk for SPMs in patients with CRC decreased progressively with increasing age at the time of initial diagnosis in earlier studies 9 , 11 and the present study. Age is the strongest risk factor for cancer.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The survival of CRC patients has improved gradually with the widespread use of advanced diagnostic and therapeutic methods, including fecal occult bleeding tests, colonoscopy screening, targeted treatments, and multidisciplinary team therapy approaches. The increased survival rate has resulted in increased risks of developing subsequent primary malignancies, among which the subsequent primary colorectal cancer (SPCRC) was the most commonly observed form of cancer [ 1 , 2 ]. Synchronous colorectal adenoma and family history of CRC are indicators for SPCRC [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%